Pericentrické inverze lidských chromozómů a jejich rizika - Balícek, P (Casopis lekaru ceskych, 2001)
Pericentric inversions of human chromosomes represent rearrangements are formed between two breaks on the short and on long arms of the chromosome with following rotation and new connection of the separated segment in the reversed position. The abnormality does not result in most of the carriers to any clinical manifestations. However, the basic risk the carriers of such inversion are exposed is the possibility of formation of a recombinant aneusomy--later transformation of the inverted chromosome during gametogenesis. Conception by the recombinant gamete usually results in spontaneous abortion or to a birth of seriously affected individual. The risk of recombination has to be in every newly registered inversion individually considered. The larger part of chromosome is taken into the pericentic inversion, the smaller is the extent of resulting duplication and smaller is the deficiency of chromosomal parts, which results from the recombination. The higher is then the viability of the affected foetus. In families with detected recombination, chromosomal examination is fully recommended. Prenatal examination is also indicated when the transformation is listed among the risk inversions or it has larger extent then recorded inversions. Beside the risk inversions, also the "safe" inversions exist, which include minor and frequently occurring transformation of chromosome No 2--inv(2)(p11q13) and inversion of chromosome 10--inv(10)(p11q21).
Keywords: heterozygot; Female; ženské pohlaví; chromozomální poruchy; prenatální diagnóza; lidé; Heterozygote; těhotenství; Prenatal Diagnosis; Risk Factors; Recombination, Genetic; Chromosome Inversion; Male; chromozomální aberace; rizikové faktory; mužské pohlaví; Chromosome Disorders; Pregnancy; rekombinace genetická; chromozomální inverze; Chromosome Aberrations; Humans